The concept of public management for social enterprises in Ukraine - Onyshchenko, Oksana (Management and Entrepreneurship: Trends of Development, 2017)
Purpose. The paper purpose is to develop a model of public management for social entrepreneurship in the context of ensuring public support for social enterprises and the creation of appropriate infrastructure.Design/methodology/approach. In the course of the research, general scientific methods of analysis were used: formal, logical, and comparative; general methods: abstraction and generalization, idealization, analogy and modeling methods; as well as empirical methods: secondary sociological analysis, analysis of regulatory documents; institutional, inductive and deductive approaches were applied.Findings. The subject of the study is the mechanisms for public management of the social entrepreneurship. The relevance of the research is determined by the urgent need to create a full-fledged market of social services in the country with the aim of attracting national enterprises in it. Given the fact that authorities of the State are not able to provide high-quality social services today, it is important to involve non-state non-profit organizations and private business to the social welfare sector, while ensuring comprehensive follow-up support. That is why the creation of appropriate infrastructure for the development of national social oriented business is of critical importance in the current circumstances. Therefore, the mission of state authorities in this context is to enforce and develop the effective model of the cooperation and interaction between the state and the socio-entrepreneurial sector with a view to provide support to it and to contribute to its development. As a result the steps to ensure a favorable institutional environment for social enterprises in Ukraine are proposed.Research limitations/implications. The paper determines the concept of social enterprise and identifies criteria for social entrepreneurship. A model of public management for social entrepreneurship is developed.Originality/value. Such knowledge will help to attract the non-profit sector as well as private business to the social sector, which in turn will contribute to the social stability in the country. Further research on the development of social oriented business is significantly actualized considering current unstable political and economic situation, since the social stability of society is a prerequisite for the successful functioning of the state